A Delphi study to build consensus on strategies for adult vocational training of higher education institutes in Guangxi Zhuang Autonomous Region China - Wei, Guangpei; Tuntinakhongul, Ampapan (My University, 2024)
Adult vocational training of higher education institutes has great potential to help workforce coping with uncertainties of the fast-changing Labor market in the era of Industrial Revolution 4.0. However, the lack of clarity regarding strategies for effectively establishing adult vocational training in higher education institutes may hinder progress. The aim of this study was to develop agreed strategies of adult vocational training for higher education institutes in Guangxi Zhuang Autonomous Region, China. The 3-round Delphi method used semi-structured interviews and questionnaires to explore and reach an agreement on the future direction of the strategies. The semi-structured interview was used in the first round to explore the ideas in relation to such strategies. the questionnaires were used in the second and the third rounds to explore further and reach the consensus on expert opinions defined at interquartile range (IQR) ≤ 1. Besides that, Analytic Hierarchy Process (AHP) methods were used to calculate the weights of each consented statements. Through Delphi method, the comprehensive strategies have been articulated with the highlights of 1 vision, 6 goals and 40 actionable strategies. furthermore, the experts commonly highlighted that the vision of future adult vocational training shall prioritizes cultivating skilled professionals with industrial needs, offering everyone accessible opportunities for career development. Besides that, the result also showed that reskilling and upskilling and extending the leaners’ interpersonal networks have been ranked as the two most important goals for future adult vocational training in higher education institutes.
Keywords: actionable strategies; adult vocational training; AHP method; Delphi method; goals; higher education institutes; vision